Geographical characteristics and formation mechanisms of smallpox epidemics in Hubei Province, China, 1488–1949 - Yuxin Zeng; Zhiyu Chen; Xihao Yan; Shengsheng Gong; Tao Zhang (PLoS ONE, 2025)
Smallpox is a highly contagious and ancient disease influenced by natural and social factors. These factors led to the wide spread of smallpox in Hubei Province of China during the historical period. We conducted the spatial and temporal distribution patterns of smallpox epidemics and their formation mechanism in Hubei Province of China during 1488–1949. Based on epidemic history and environmental data, we used M-K test, wavelet analysis, spatial autocorrelation model, epidemic center of gravity model and geographically weighted regression models.In terms of temporal changes, the earliest smallpox in Hubei Province can be traced to the Ming Dynasty. Smallpox epidemics in the Republic of China showed fluctuating and changing trends; in 1939, incidences of smallpox grew abruptly. Smallpox epidemics in the Republic of China occurred on a fluctuating cycle of two time scales: 8 years and 18 years. The epidemic season was mainly spring and summer.Smallpox epidemics in Hubei Province had a wide spatial scope and exhibited spreading and diffusion characteristics; three towns of Wuhan, Suixian and Yichang were the centers of the epidemics. Smallpox epidemics exhibited significant spatial concentrations; high concentration areas occurred mainly in Wuchang, Hankou and Hanyang. The center of gravity of the epidemics exhibited a small swing from east to west and gradually shifted to the west.River networks, road networks, wars and other factors promoted smallpox epidemics; river networks and war factors were significant in eastern Hubei Province; road network factors were significant in southern Hubei Province; and droughts somewhat inhibited smallpox epidemics in western Hubei Province. Temperature fluctuations, droughts and floods, and war outbreaks played dominant roles in the temporal characteristics of smallpox epidemics in Hubei Province, and topography, population distribution and population movement played dominant roles in the spatial distribution pattern of smallpox epidemics in Hubei Province. We must establish and improve an epidemic monitoring and early warning system, pay attention to key areas, strengthen inspection and quarantine, stockpile smallpox vaccines, develop therapeutic drugs, and strengthen prevention of bioterrorism. Our study revealed how smallpox spreads in terms of both spatial and temporal patterns and mechanisms, and based on this, we can propose preventive and control measures against smallpox reemergence and its similar viruses.